(untitled) (Costos y Gestión, 2025)
This paper examines the necessity for companies to adopt management models aimed at improving their business processes and addressing internal and external factors that hinder the achievement of corporate objectives. It presents a literature review on management and quality models, from which the Torment 1.0 management model is developed, founded on Business Process Management (BPM), Activity-Based Management (ABM), and the ISO 9001:2015 process-based quality standard. The model is structured into three core blocks: Company, which defines the organizational architecture; Mapping, Analysis, and Improvement, which oversees process, time, cost, and optimization management; and Support Information Platform, which centralizes information, processes it, and generates reports to support decision-making. The model was applied in four case studies: assembly of televisions, electronic circuits, motorcycles, and bicycles. The results include the creation of process maps, measurement and standardization of times, redistribution of resources and cost centers, cost calculation through TDABC, identification of problems, enhancement of plant layout, resource balancing, process redesign, and benefit optimization through the reduction of costs and expenses, thereby consolidating a comprehensive methodology for business efficiency.